International Handbook on the Economics of Migration 2013
DOI: 10.4337/9781782546078.00025
|View full text |Cite
|
Sign up to set email alerts
|

The impact of migration on family left behind

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 53 publications
5
91
0
Order By: Relevance
“…Most notably, ethnographic research suggests that happiness lost by family separation might outweigh the happiness gained from money sent as remittances (Dreby, 2010). In addition, some studies document declining educational attainment and physical health among left-behind children and elderly parents, respectively, as well as changing intrafamily roles such as a greater responsibility for household chores and lower labor-force participation for the spouse who stays behind (Antman, 2013). Happiness regressions can isolate the impact of these various advantages and disadvantages of migration on the happiness outcomes of those who remain in the origin country.…”
Section: The Happiness Of Internal Migrants Natives and Stayersmentioning
confidence: 99%
“…Most notably, ethnographic research suggests that happiness lost by family separation might outweigh the happiness gained from money sent as remittances (Dreby, 2010). In addition, some studies document declining educational attainment and physical health among left-behind children and elderly parents, respectively, as well as changing intrafamily roles such as a greater responsibility for household chores and lower labor-force participation for the spouse who stays behind (Antman, 2013). Happiness regressions can isolate the impact of these various advantages and disadvantages of migration on the happiness outcomes of those who remain in the origin country.…”
Section: The Happiness Of Internal Migrants Natives and Stayersmentioning
confidence: 99%
“…In this paper, we explore the impact of adult child emigration on the mental health of older parents and in so doing we build on the work of Antman (2010Antman ( , 2011Antman ( and 2013. Using the first wave of the Mexican Health and Ageing Study (MHAS), Antman found evidence of negative impacts on both the mental and physical health of Mexican parents due to the emigration of their children.…”
Section: Section 1: Introductionmentioning
confidence: 99%
“…First, we add to the novel literature on the consequences of emigration on the well-being and behaviors of the left behind (Antman, 2010(Antman, , 2013Böhme, Persian, & Stöhr, 2015;Démurger, 2015;Stöhr, 2015). Second, we contribute to the scholarship on the determinants of civic engagement (Andreoni, 1989(Andreoni, , 1990Meier & Stutzer, 2008;Vesterlund, 2006).…”
Section: Related Literaturementioning
confidence: 99%
“…On the other hand, the absence of a family member could be disruptive to the household unit and may result in depression, worsened health, decreased labor supply, and others (Démurger, 2015;Lu, 2012). The literature on the well-being consequences of migration for the families left behind is still in its infancy and primarily focuses on income, consumption, school outcomes, and subjective well-being of the left behind (for overviews, see Antman (2013) and Démurger (2015)). The findings vary depending on individual circumstances and the outcome metric studied.…”
Section: Related Literaturementioning
confidence: 99%